A novel energy‐aware routing mechanism for SDN‐enabled WSAN. (13th June 2018) - Al‐Hubaishi, Mohammed; Çeken, Celal; Al‐Shaikhli, Ali
Summary: Energy consumption is one of the most important design constraints when building a wireless sensor and actuator network since each device in the network has a limited battery capacity, and prolonging the lifetime of the network depends on saving energy. Overcoming this challenge requires a smart and reconfigurable network energy management strategy. The Software‐Defined Networking (SDN) paradigm aims at building a flexible and dynamic network structure, especially in wireless sensor networks. In this study, we propose an SDN‐enabled wireless sensor and actuator network architecture that has a new routing discovery mechanism. To build a flexible and energy‐efficient network structure, a new routing decision approach that uses a fuzzy‐based Dijkstra's algorithm is developed in the study. The proposed architecture can change the existing path during data transmission, which is the key property of our model and is achieved through the adoption of the SDN approach. All the components and algorithms of the proposed system are modeled and simulated using the Riverbed Modeler software for more realistic performance evaluation. The results indicate that the proposed SDN‐enabled structure with fuzzy‐based Dijkstra's algorithm outperforms the one using the regular Dijkstra's and the ZigBee‐based counterpart, in terms of the energy consumption ratio, and the proposed architecture can provide an effective cluster routing while prolonging the network lifetime. Abstract : In this study, we propose an SDN‐enabled WSAN architecture that has a new routing discovery mechanism. To build a flexible and energy‐efficient network structure, a new routing decision approach that utilizes a fuzzy‐based Dijkstra's algorithm is developed in the study. The proposed system finds the optimum route under dynamic working conditions, supports multiple applications efficiently, and is capable of both providing an effective cluster routing and prolonging the network lifetime. The comparative results demonstrate that the proposed SDN‐enabled structure with fuzzy‐based Dijkstra's algorithm outperforms the one using the regular Dijkstra's and the ZigBee‐based counterpart, in terms of the energy consumption. Moreover, SDN seems to be the strongest candidate among the deployment options for solving the network flexibility problem of WSAN structures.